Wealth-related inequalities of women's knowledge of cervical cancer screening and service utilisation in 18 resource-constrained countries: evidence from a pooled decomposition analysis - Rashidul Alam Mahumud; Syed Afroz Keramat; Gail M Ormsby; Marufa Sultana; Lal B. Rawal; Khorshed Alam; Jeff Gow; Andre M. N. Renzaho (BMC, 2020)
Abstract Introduction Resource-constrained countries (RCCs) have the highest burden of cervical cancer (CC) in the world. Nonetheless, although CC can be prevented through screening for precancerous lesions, only a small proportion of women utilise screening services in RCCs. The objective of this study was to examine the magnitude of inequalities of women's knowledge and utilisation of cervical cancer screening (CCS) services in RCCs. Methods A total of 1,802,413 sample observations from 18 RCC's latest national-level Demographic and Health Surveys (2008 to 2017-18) were analysed to assess wealth-related inequalities in terms of women's knowledge and utilisation of CCS services. Regression-based decomposition analyses were applied in order to compute the contribution to the inequality disparities of the explanatory variables for women's knowledge and utilisation of CCS services. Results Overall, approximately 37% of women had knowledge regarding CCS services, of which, 25% belonged to the poorest quintile and approximately 49% from the richest. Twenty-nine percent of women utilised CCS services, ranging from 11% in Tajikistan, 15% in Cote d'Ivoire, 17% in Tanzania, 19% in Zimbabwe and 20% in Kenya to 96% in Colombia. Decomposition analyses determined that factors that reduced inequalities in women's knowledge of CCS services were male-headed households (− 2.24%; 95% CI: − 3.10%, − 1.59%; P < 0.01), currently experiencing amenorrhea (− 1.37%; 95% CI: − 2.37%, − 1.05%; P < 0.05), having no problems accessing medical assistance (− 10.00%; 95% CI: − 12.65%, − 4.89%; P < 0.05), being insured (− 6.94%; 95% CI: − 9.58%, − 4.29%; P < 0.01) and having an urban place of residence (− 9.76%; 95% CI: − 12.59%, − 5.69%; P < 0.01). Similarly, factors that diminished inequality in the utilisation of CCS services were being married (− 8.23%;95% CI: − 12.46%, − 5.80%; P < 0.01), being unemployed (− 14.16%; 95% CI: − 19.23%, − 8.47%; P < 0.01) and living in urban communities (− 9.76%; 95% CI: − 15.62%, − 5.80%; P < 0.01). Conclusions Women's knowledge and utilisation of CCS services in RCCs are unequally distributed. Significant inequalities were identified among socioeconomically deprived women in the majority of countries. There is an urgent need for culturally appropriate community-based awareness and access programs to improve the uptake of CCS services in RCCs.